Comparison of current treatment strategy for osteonecrosis of the femoral head from the perspective of cell therapy - Wang, Jiaqian; Xu, Peirong; Zhou, Liang (Frontiers in Cell and Developmental Biology, 2023)
Aims: The purpose of our study is to compare the effects of core decompression (CD) and bone grafting (BG) on osteonecrosis of the femoral head (ONFH). And evaluate the efficacy of CD based on cell therapy to provide guidance for the dose and number of cells. Methods: We searched PubMed, Embase, and the Cochrane Library between 2012 and 2022, with keywords including “osteonecrosis of the femoral head”, “core decompression” and “bone grafting”. We selected comparative studies of CD and BG, and the comparison of CD combined with bone marrow (BM) transplantation and CD alone. Changes in hip pain were assessed by VAS, hip function were assessed by HHS and WOMAC, and THA conversion rate was used as an evaluation tool for femoral head collapse. From these three aspects, the dose of bone marrow and the number of cells transplantation were subgroup analyzed. Results: Eleven studies were used to compare the efficacy of CD and BG. There was no significant difference in HHS, and the THA conversion rate of BG was significantly lower than that of CD. Thirteen CD studies based on cell therapy were included in the meta-analysis. Bone marrow aspiration concentrate (BMAC) can significantly improve VAS (mean difference (MD), 10.15; 95% confidence intervals (CI) 7.35 to 12.96, p < 0.00001) and reduce THA conversion rate (odds ratio (OR), 2.38; 95% CI 1.26 to 4.47, p = 0.007). Medium dose bone marrow fluid has a lower p-value in THA conversion rate. The p values of bone marrow mononuclear cells (BMMC) of 109 magnitude in VAS score were lower. Conclusion: In general, there is no consensus on the use of BG in the treatment of ONFH. The enhancement of cell-based CD procedure shows promising results. Using 20 mL BMAC and 109 magnitude BMMC is likely to achieve better results.